2014
DOI: 10.2196/mhealth.3888
|View full text |Cite
|
Sign up to set email alerts
|

The Medium and the Message: Fitting Sound Health Promotion Methodology Into 160 Characters

Abstract: Text messaging health promotion projects continue to proliferate due to their relative low-cost, simplicity, non-intrusiveness, and proven effectiveness in several randomized controlled trials. In these past trials, participants have typically been recruited through traditional means, received the text messaging intervention, and then completed evaluation. In this issue of the Journal of Medical Internet Research, Sheoran et al have demonstrated how use of text messaging alone can be a feasible method for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…mHealth technologies may be utilized at several phases of research projects, including community engagement, recruitment, monitoring of adherence to study protocols, data collection, study close out and translation of research into practice [25,26]. Studies have reported that use of mHealth as a research tool decreases the potential for recall bias in retrospectively collected data at study visits [2729]; is a cost-effective method to increase adherence to study protocol instructions when compared to one time in person verbal and written instructions to participants [30]; and is useful in contacting difficult to reach study participants [31].…”
Section: Mhealthmentioning
confidence: 99%
“…mHealth technologies may be utilized at several phases of research projects, including community engagement, recruitment, monitoring of adherence to study protocols, data collection, study close out and translation of research into practice [25,26]. Studies have reported that use of mHealth as a research tool decreases the potential for recall bias in retrospectively collected data at study visits [2729]; is a cost-effective method to increase adherence to study protocol instructions when compared to one time in person verbal and written instructions to participants [30]; and is useful in contacting difficult to reach study participants [31].…”
Section: Mhealthmentioning
confidence: 99%
“…27 Text messaging (short message service, SMS; containing 160 characters) varies in frequency (daily, weekly), interactivity (one-way vs. two-way), personalization and tailoring (all of the above). [28][29] Text messages from web-based platforms allow for pre-scheduling of sending, automation, and better monitoring.…”
Section: Internet and Mobile Health Trends For Self-directed Habit Lmentioning
confidence: 99%
“…Sexual health interventions that are integrated with modern technologies have been successful [17-22]. Text messaging has been widely used to promote sexual health, including appointment reminders, partner tracing, and result notification [22].…”
Section: Introductionmentioning
confidence: 99%
“…Text messaging has been widely used to promote sexual health, including appointment reminders, partner tracing, and result notification [22]. Studies of Internet-based human immunodeficiency virus (HIV) infection interventions targeting MSM using online questionnaires and tutorial sessions revealed a reduced rate of unprotected anal intercourse and increased condom use [20,21].…”
Section: Introductionmentioning
confidence: 99%